Faktor Demografis Dalam Perilaku Pembelian Impulsif - Mulyono, Fransisca (Business Administration Study Program - Universitas Katolik Parahyangan, 2012)
Impulse buying behavior has received the attention of Western academic scholarsdue to the existing contradiction between what consumer say and what they actuallydo. Many consumers realize that this is not a right and good behavior. Neverthelessthey continue to purchase the products in this fashion. Even in USA, this behaviorhas become a common phenomenon. The goal of this research is to find out whetherconsumerâs demographic factors influence the impulse buying behavior or not. Inthis research, the impulse buying behavior is divided into two components: affectiveand cognitive components. The result reveals that respondentâs gender and age are theonly factors that influence the affective component, while in the cognitive component,the result shows that there is no respondentâs demographic factors influence.Keywords: Impulse buying, affective and cognitive components, gender, age,budget of spending, level of education